2021
DOI: 10.2147/dmso.s280735
|View full text |Cite
|
Sign up to set email alerts
|

Non-Surgical Interventions for Hospitalized Adults with Class II or Class III Obesity: A Scoping Review

Abstract: Adult inpatients with Class II or III obesity and comorbidities have a high health burden with frequent hospitalizations. Surgical risk and patient choice can be contraindications to bariatric surgery, which is considered the gold standard treatment. The best approach to non-surgical management for this adult inpatient group is currently unknown. The aim of this scoping review was to summarize current research in the inpatient setting. The unpublished literature and six electronic database searches identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Regarding the non-surgical strategies available at the end of the process of indication/contraindication (S14) multiple endoscopic treatments have been proposed and offered to those patients who refuse surgery or are not suitable for surgery. Procedure selection depends on costs, ability to pay, patient’s risk profile, center’s experience, patient’s preferences, and comorbidities to treat [ 38 ]. The KOLs agreed with the respondent about the safety of all the nutritional strategies in patients unsuitable for surgical/invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the non-surgical strategies available at the end of the process of indication/contraindication (S14) multiple endoscopic treatments have been proposed and offered to those patients who refuse surgery or are not suitable for surgery. Procedure selection depends on costs, ability to pay, patient’s risk profile, center’s experience, patient’s preferences, and comorbidities to treat [ 38 ]. The KOLs agreed with the respondent about the safety of all the nutritional strategies in patients unsuitable for surgical/invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 A scoping review shows that psychological interventions can increase patients’ awareness and compliance with their eating behaviors and enhance self-behavior management to ensure weight loss maintenance in non-surgical interventions for hospitalized adults with class II or class III obesity. 56 IF in combination with supportive psychodynamic psychotherapy and physical activity is an effective strategy for long-term weight loss and body mass index (BMI), waist-to-hip ratio, and body fat reduction. 57 …”
Section: If Combined With Other Interventionsmentioning
confidence: 99%
“…Hospitals are seeing increased rates of severe pediatric obesity impacting treatment and outcomes for acute hospitalizations, regardless of presenting diagnosis (1,(3)(4)(5)(6). Inpatient hospitalization presents an opportunity to engage in nutritional counseling, obesity-related comorbidity screening, and initiation of anti-obesity pharmacotherapy (7,8). This is similar to screening and counseling for other conditions while inpatient, yet studies show these assessments rarely occur (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, three recent reviews found that two-thirds of all prescribed medications in children with obesity were either sub-therapeutic or supratherapeutic (1,12,15). Despite negative inpatient outcomes, studies show that obesity is rarely documented or considered an important factor in inpatient care, unless it is thought to directly affect the treatment for the acute illness (6,8). A recent study found that fewer than 40% of children's hospitals have universal policies to identify and treat patients with obesity, with BMI calculated in only 35% of pediatric inpatient encounters (12).…”
Section: Introductionmentioning
confidence: 99%